Andean exceptionalism and the new Inka scholarship. (30th January 2015) - Covey, R. Alan
Abstract : Grand theories of human social organisation have sometimes struggled to find a place for the Inka empire, which achieved an unprecedented degree of state power across the Andean region of western South America for a few generations in the late fifteenth and early sixteenth centuries AD. This is in part because the Inka realm looked so different from the ancient empires of Eurasia. The axis of Inka power ran north–south through some of the most diverse and difficult terrain on the planet, and Inka material culture and institutions lacked many of the Western hallmarks of civilisation. In Ancient society (1877), Lewis Henry Morgan relegated the Inkas to a status of 'middle barbarism' for possessing only Bronze Age metallurgy, placing a realm of perhaps 10 million inhabitants in the company of the Puebloan peoples of the American Southwest and the society that built Stonehenge. More than a century later, the sociologist Michael Mann (1986 ) offered the Inkas as an exception to his general model for wielding so much power without using writing, currency or low-cost forms of transportation.